2017
DOI: 10.1097/nna.0000000000000456
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Nurse Leaders’ and Direct Care Nurses’ Perceptions of a Healthy Work Environment in Acute Care Settings, Part 3

Abstract: Samples included 314 subjects for the HWES for NL study and 986 subjects for the HWES for DCN study. Principal component analysis for the HWES for NLs (version 3) revealed 40 items comprising 4 components, and PCA for the HWES for DCNs (version 3) revealed 39 items comprising 5 components. Internal consistencies of the tools were 0.974 and 0.957, respectively. Based on the findings of these studies, the tools demonstrated promising psychometric properties to measure a HWE in acute care settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 12 publications
1
9
0
2
Order By: Relevance
“…Such interventions match the variables that the RN4CAST consortium identifies as decisive in a good working environment, such as the need for enough staff, nurses holding positions of power and participating in the decision‐making process, and good interdisciplinary communication (Aiken et al., ). More recent studies identify the environments in which policies, procedures and work processes are clearly defined as Healthy Work Environments (HWEs), which empowers nurses to do their job, increases their satisfaction and helps to retain them in health care (Huddleston, Mancini, & Gray, ).…”
Section: Discussionmentioning
confidence: 99%
“…Such interventions match the variables that the RN4CAST consortium identifies as decisive in a good working environment, such as the need for enough staff, nurses holding positions of power and participating in the decision‐making process, and good interdisciplinary communication (Aiken et al., ). More recent studies identify the environments in which policies, procedures and work processes are clearly defined as Healthy Work Environments (HWEs), which empowers nurses to do their job, increases their satisfaction and helps to retain them in health care (Huddleston, Mancini, & Gray, ).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown that the healthy work environment of Iranian nurses is Inappropriate (Hoseini Es darjani et al, 2018;Salehi et al, 2020). A study by Kim et al (2020) reported a Inappropriate healthy work environment in nurses in Southern California (Kim et al, 2020), while studies in other countries show a appropriate healthy work environment (Huddleston et al, 2017;Kelly and Todd, 2017;Monroe et al, 2020). Studies show that, this difference can be due to the type of management, work culture, authority and different independence of nurses in Iran and abroad.…”
Section: Discussionmentioning
confidence: 98%
“…Obstajajo različni instrumenti za merjenje psihološkega stresa ter obremenitev na delovnem mestu (Nuebling, et al, 2006), oceno delovnega mesta zaposlenega (Bai, et al, 2015), vpliva delovnega okolja na klinično prakso v zdravstveni negi (Elmi, et al, 2017;Jing, et al, 2017;Ogata, et al, 2018) in oceno zdravega delovnega okolja (Huddleston, et al, 2017).…”
Section: Uvodunclassified